2022
DOI: 10.1097/meg.0000000000002470
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of neutrophil percentage-to-albumin ratio predict increased mortality risk in patients with liver cirrhosis: a retrospective cohort study

Abstract: Background Recent studies indicated that the neutrophil percentage-to-albumin ratio (NPAR) was a predictor of mortality in several diseases. There has been no evidence to prove the predictive function of NPAR in patients with liver cirrhosis. Therefore, this study aimed to investigate the association between NPAR and clinical outcomes in cirrhotic patients. Methods We retrospectively recruited hospitalized decompensated cirrhotic patients from the tertiary grade-A hospital. Patients with malignancy or severe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…NPAR is a relatively new inflammatory marker, and few studies have explored its prognostic value. 30 However, NPAR has been shown to correlate with prognosis in various other diseases. A previous study noted that higher NPAR was associated with an increased risk of all-cause mortality in critically ill patients with severe sepsis or septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPAR is a relatively new inflammatory marker, and few studies have explored its prognostic value. 30 However, NPAR has been shown to correlate with prognosis in various other diseases. A previous study noted that higher NPAR was associated with an increased risk of all-cause mortality in critically ill patients with severe sepsis or septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we confirmed that NPAR and NLR are both predictive of COPD mortality, and the performance of NPAR is slightly better than that of NLR. NPAR is a relatively new inflammatory marker, and few studies have explored its prognostic value 30 . However, NPAR has been shown to correlate with prognosis in various other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with septic shock [ 23 ], acute renal injury [ 24 ], and palliative pancreatic cancer [ 25 ], NPAR, which integrates albumin and NLR, is employed as a systemic inflammation predictor. Additionally, NPAR is linked to mortality among individuals with liver cirrhosis and atrial fibrillation [ 26 , 27 ]. We observed a similar significant association between NPAR and the presence of NAFLD in a recent study by Liu et al They reported a statistically significant correlation (14.3 ± 0.1, p=0.013) between NPAR and NAFLD, and these results are in line with our findings [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“… 101 Interestingly, neutrophil to albumin ratio is linked to mortality in patients with decompensated cirrhosis. 102 , 103 Given the ability of albumin to bind bacterial products, ROS, and nitric oxide, 104 the changes in its abundance and structure might contribute to neutrophil dysfunction. The addition of albumin to incubation media has been shown to decrease the number of neutrophils with high basal ROS production and reverse phagocytic capacity defects caused by plasma from patients with cirrhosis.…”
Section: Causes Of Neutrophil Dysfunction In Cirrhosismentioning
confidence: 99%